2001
DOI: 10.2176/nmc.41.431
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic Brain Tumor Detected at Brain Check-up.

Abstract: Brain check-up was performed in 4000 healthy subjects who underwent medical and radiological examinations for possible brain diseases in our hospital from April 1996 to March 2000. Magnetic resonance imaging revealed 11 brain tumors which consisted of six meningiomas, three pituitary adenomas, one astrocytoma, and one epidermoid cyst. The detection rate of incidental brain tumor in our hospital was 0.3%. Nine patients underwent surgery, with one case of morbidity due to postoperative transient oculomotor nerve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
27
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 12 publications
2
27
0
1
Order By: Relevance
“…19,28 Among the patients whose incidental LGGs were discovered due to trauma, there were no reported recurrences, and only 1 patient with a tectal glioma had a KPS score < 100 at follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…19,28 Among the patients whose incidental LGGs were discovered due to trauma, there were no reported recurrences, and only 1 patient with a tectal glioma had a KPS score < 100 at follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, brain screening with computed tomography (CT) and magnetic resonance imaging (MRI) is easily performed for nonspecific complaints and 'neurological checkups' are performed frequently in Japan (3). Thus, an increasing number of intracranial meningiomas are identified incidentally (4,5). However, few studies have reported the outcome of surgical resection of intracranial meningiomas in the elderly (6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…In the healthy population, the incidence of ILGG is currently estimated to be between 0.025% and 0.3%. 23,35,53,54 In a series of 4309 gliomas from the French Brain Tumor Databank, 130 cases of incidentally diagnosed gliomas (3%) have been reported. 2 Due to the rapid development of neuroimaging, the probability of encountering ILGG will increase in the near future.…”
mentioning
confidence: 99%